Determinants of Accounting Conservatism in Mining Companies Listed on the Indonesia Stock Exchange in 2019–2023 - Musdalifa Fabanyo; Irfan Zamzam; Asrudin Hormati; Zainuddin Zainuddin (International Journal of Multidisciplinary Sciences and Arts, 2025)
This study investigates the determinants of accounting conservatism in mining companies listed on the Indonesia Stock Exchange during the 2019–2023 period. Specifically, it examines the effects of exploration activity level, firm size, leverage, and capital intensity on accounting conservatism. Data were collected from 11 mining companies that met the selection criteria, resulting in 55 firm-year observations. The study employed purposive sampling and multiple linear regression analysis with the aid of EViews software. The findings reveal that exploration activity level, firm size, and leverage do not significantly influence accounting conservatism. However, capital intensity shows a significant positive effect on accounting conservatism, suggesting that firms with higher capital intensity tend to adopt more conservative accounting practices. These results indicate that despite the inherent risks and uncertainties in mining operations, companies may not necessarily apply conservative reporting unless influenced by substantial capital investment. The study contributes to the literature by highlighting the role of capital intensity as a key driver of accounting conservatism in resource-intensive industries and provides insights for stakeholders seeking more reliable financial information in high-uncertainty sectors.